Le cure materne e il reinserimento sociale della condannata: attualità di un vecchio problema - Raffaella Sette (Rivista di Criminologia, Vittimologia e Sicurezza, 2015)
Thanks to the forensic and psychiatric expert’s report, in this article some of the crucial points of the so-called “Cogne case” are highlighted in order to underline better the reasons why the Surveillance Court of Bologna allowed the offender to serve the last part of her sentence on special home detention. Furthermore, the study done by the expert transfers extensive knowledge about prisons, detention conditions and their effects based on what a female inmate told about herself and her temporary stay on the ”planet jail”.